Transition to Adult Care in Children on Long-Term Ventilation - Onofri, Alessandro; Broomfield, Alexander; Tan, Hui-leng (Frontiers in Pediatrics, 2020)
The number of children on long-term ventilation (LTV) has exponentially increased over the past few decades. Improvements in management of ventilation coupled with improvements in standards of medical care are increasingly allowing young people on LTV to survive into adulthood. The process of transition from the paediatric to the adult healthcare system is challenging and requires special attention. This review aims to provide an overview on transition to adult care for children on LTV. Firstly, examining effective models of transition in other childhood onset chronic conditions as a template, whilst highlighting the unique aspects of transition in LTV patients and secondly summarizing the main relevant findings in the literature on the topic and emphasizing the importance of a multidisciplinary approach to this process.